Epidemiological implications of Aedes albopictus (Skuse) in Colombia - Guillermo L. Rúa-Uribe; Raúl A. Rojo; Carolina Suárez-Acosta (Universidad de Antioquia, 2012)
The presence of respiratory problems in high level pollution areas is linked to factors such as exposure, susceptibility, and social coping. Objective: To present statistical evidence regarding the relationship between the probability of experiencing symptoms or contracting a respiratory disease and factors such as exposure to pollution, susceptibility, and social coping among people inhabiting areas with particulate matter pollution. Methodology: The study used unique information collected from a survey conducted on 1000 people in downtown Medellin who were exposed to this problem. This information was used to perform a descriptive statistic analysis and to build 27 probit models. The dependent variables were: the patient has a symptom or disease -emf-, the patient has a symptom -leve-, and the patient has a respiratory disease -grave-. Results: The results evidence that exposure is a key variable affecting the presence of respiratory symptoms or diseases (vulnerability); however, exposed individuals may also experience health problems not only due to air pollution per se, but also to implicit personal and social conditions.